It does matter how you get to the top: Differentiating status from reputation - Karen D. W. Patterson; David Eduardo Cavazos; Marvin Washington (Administrative Sciences, 2014)
Status and reputation have long been recognized as important influences in management research and recently much attention has been paid to defining the two concepts and understanding how they are utilized by organizations. However, few strategic management studies have identified the different methods through which status and reputation are constructed. While reputation has been linked with a history of quality, and status has been identified as an externally assigned measure of social position, empirical studies have been highly idiosyncratic in their identification of the mechanisms used to obtain either construct. This paper attempts to rectify that gap in the literature by identifying two distinct methods used to obtain reputation and status. We argue that certification contests can be used to increase organizational reputation and tournament rituals can be used to increase organizational status. We build theoretical propositions regarding the use of certification contexts and tournament rituals to show how reputation and status are achieved through similar, but distinct, methods and further the research on teasing apart these two important and intertwined concepts.
Keywords: 350; status; reputation; certification contests; tournament rituals